COGNITIVE STIMULATION WORKSHOPS FOR ELDERLY PEOPLE WITH SUBJECTIVE MEMORY AND HUMOR COMPLAINTS - Rosimere Ferreira Santana; Shardelle Araújo Alexandrino; Thais da Silva Soares; George Luiz Alves Santos; Elisa Monteiro Magalhães Bamberg; Thais de Medeiros Oliveira (Universidade Federal de Santa Maria, 2018)
Aim: to analyze a program of cognitive stimulation workshops for elderly people with subjective memory and humor complaints and to associate it with the functional performance of functional capacity. Methods: this is a almost-experimental, quantitative study conducted in a university extension program for elderly people. For data collection, the following tests were used: Mini Mental State Examination (MMSE), Geriatric Depression Scale (EDG), Daily Life Instrumental Activities Scale (Lawton), Verbal Fluency Test (EVP) and Clock Test. Descriptive and inferential data analysis using R. software. Results: after the cognitive stimulation workshops, we obtained a discreet increase in the MMSE scores and a decrease in EDG. As for the Lawton Clock and EVP test scores, there were maintenance on values, which may be indicative of maintaining functional capacity. Conclusion: we recommend programs of cognitive stimulation with systematized intervention protocols, with specific attention to the demands of the elderly people and follow-up of the functional capacity.